A study of the multiple functions and interactions of semicarbazide sensitive amine oxidase - O'Sullivan, Jeffrey (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2005)
This thesis focuses on three of the recognised multiple functions of mammalian semicarbazide sensitive amine oxid ase (SSAO) and the contribution of monoamine oxidase (MAO) to some of these. SSAO is a vascular-adhesion protein, under the guise vascular adhesion protein-1 (VAP-1). As many cell-cell interactions occur by specific recognition of carbohydrate ligands, the interactions between monosaccharide derivatives and SSAO were studied. Mannosamine, glucosamine and galactosamine were found to be time-dependent inhibitors of SSAO activity, whereas their N-acetyl derivatives and the unsubstituted hexoses failed to inhibit the enzyme. Differences in potency displayed by amino sugars suggest specificity towards the structure of sugar. The inhibition was concentration dependent but fully reversible. The H2O2 formed as a product of the SSAO -catalysed oxidation reaction was show n to be necessary to enable the inhibition of the enzyme by galactosamine. Several other compounds were tested as possible analogues, including serinol, pyrroline-5-carboxylic acid and three 2-amino sugar analogues. Inhibition was observed in some cases but this was was not time dependent.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin